Schiff base silane complex transition metal modified ablation-resistant resin matrix material as well as preparation method and application thereof

By designing a silane coupling agent with a hydroxyl-substituted aromatic Schiff base structure to react with a phenolic resin to stabilize the coordination of transition metals, the problem of poor ablation performance of traditional materials is solved and higher ablation and heat resistance is achieved. Aircraft protection materials suitable for high temperature environments.

CN119119394AActive Publication Date: 2024-12-13SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411385621.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

传统酚醛树脂基复合材料在烧蚀过程中抗氧化性、热稳定性和力学性能较差,难以满足高马赫、高机动、多空域发展的高防热、抗氧化和抗机动过载能力要求。

Method used

A silane coupling agent with a hydroxyl substituted aromatic Schiff base structure is designed to realize catalytic graphitization or ceramicization by reacting with a phenolic resin and stably coordinating the transition metal, thereby improving the ablation performance of the material.

Benefits of technology

It significantly improves the ablation and heat resistance of the material, and is suitable for high-temperature gas and pneumatic heat flow to erode structural parts in harsh environments, providing better linear ablation rate and thermal residual weight of 800°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119394A_ABST
    Figure CN119119394A_ABST
Patent Text Reader

Abstract

The invention provides a Schiff base silane complex transition metal modified ablation-resistant resin matrix material as well as a preparation method and application thereof, and belongs to the field of thermal protection materials. The silane coupling agent with a hydroxyl substituted aromatic Schiff base structure is synthesized, traditional silane and thermosetting resin are used as raw materials, and a certain amount of coupling agent is added, so that on one hand, the compatibility of organic silicon and the thermosetting resin is remarkably improved; on the other hand, due to introduction of a Schiff base structure, the capacity of the system for stably chelating the transition metal is improved, and the transition metal can be uniformly introduced into a thermosetting resin cross-linked network. And through the synergistic effect of the two components, the ablation resistance of the material is remarkably improved. The material disclosed by the invention has excellent ablation resistance, has a wide application prospect in the field of thermal protection materials, and is suitable for the fields of thermal protection and the like of related structures of aircrafts in severe thermal environments such as high-temperature fuel gas and pneumatic heat flow scouring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat protection materials, and in particular relates to an ablation-resistant resin matrix material modified by a Schiff base silane complex transition metal, a preparation method and application thereof. Background Art

[0002] Thermal protection materials are an important guarantee for the safe service of aerospace vehicles in extreme environments. With the rapid development of flight technology, the thermal environment faced by the new generation of aircraft is becoming more and more severe.

[0003] Resin-based ablative heat-resistant materials have high heat-resistant efficiency and are currently the most widely used type of heat-resistant materials. Phenolic resin is often used as ablative heat-resistant structures and heat-resistant layer matrices due to its simple molding process, good heat resistance, high mechanical strength, and outstanding instantaneous high-temperature ablation resistance. Phenolic resin-based composite materials play a very important role in aircraft thermal protection composite materials.

[0004] Although traditional phenolic resin-based composite materials have excellent ablation properties and high material strength, the carbon layer produced by phenolic resin during the ablation process is mostly amorphous structural carbon, which has poor oxidation resistance, thermal stability and mechanical properties. It is easily sheared and eroded by aerodynamic ablation, resulting in serious ablation failure. It is difficult to meet the high heat protection, oxidation resistance and maneuverability overload resistance requirements required for the future development of high Mach, high maneuverability and multi-airspace aircraft.

[0005] On the one hand, polysiloxane is a polymer with excellent thermal stability and ablation performance. It can be in-situ ceramicized during high-temperature carbonization. Therefore, it has been widely used to modify polymers such as phenolic resins, epoxy resins, polyimides, polybenzoxazines and polyurethanes to improve their flame retardancy or ablation performance in aerobic environments. Silicone that is blended or chemically bonded to the resin network can generate silica inorganic liquid film and silicon carbide ceramics in situ during the ablation carbonization process, thereby improving the ability of the carbon layer on the ablation surface of the material to resist thermal mechanical and chemical thermal oxidation losses. On the other hand, catalytic graphitization is an effective method for in-situ generation of graphite nanostructures in non-graphitizable carbon (such as thermosetting resins) under the catalytic action of transition metals (such as Ni, Co, Cu and Fe). During the carbonization process, transition metal elements react with the amorphous glassy carbon skeleton or absorb hydrocarbon atmospheres, generating different types of graphite nanostructures through the rearrangement of the amorphous structure. Generally, in order to obtain higher graphitization catalytic efficiency, a large amount of catalyst must be well dispersed in phenolic resin at the micrometer or nanometer scale by mechanical blending or dissolving in a co-solvent.

[0006] Therefore, it is of great significance to develop a modified ablation-resistant resin with excellent anti-oxidation performance and carbon layer quality. Summary of the invention

[0007] In order to overcome the above-mentioned problems existing in the prior art, combined with the advantages of improving antioxidant performance and catalytic graphitization to improve the quality of carbon layer by polysiloxane modification, the purpose of the present invention is to design a new multifunctional silane coupling agent based on the molecular structure of hybrid resin, while improving the compatibility of the two phases, realize the coordination of transition metals, and play a catalytic graphitization (Ni, Co, Cu and Fe, etc.) or ceramicization (Ti, Zr and Hf, etc.) mechanism in the resin carbonization process by chelating different types of transition metals, and further improve the ablation performance of phenolic resin. Hydroxyl-substituted Salen-based Schiff base can react with phenolic resin under appropriate conditions. Therefore, the present invention designs and synthesizes a silane coupling agent with a hydroxyl-substituted aromatic Schiff base structure, in which the hydroxyl-substituted aromatic ring structure in the coupling agent provides a reaction site with the phenolic resin, and the Schiff base structure provides a chelating site for stably coordinating the transition metal. The silane coupling agent with a hydroxyl-substituted aromatic Schiff base structure designed and synthesized by the present invention can provide a new method for uniformly introducing transition metal elements into the cross-linked network of organosilicon hybrid phenolic resin.

[0008] The present invention provides a Schiff base silane complex transition metal modified resin, which is a composite material prepared from Schiff base silane coupling agent, thermosetting resin, alkoxysilane, organic acid, water and transition metal salt as raw materials;

[0009] The ratio of the Schiff base silane coupling agent, the thermosetting resin, the alkoxysilane, the organic acid, the water and the transition metal salt is (0.01-50) g: (100-500) g: (100-500) g: (0-50) g: (0-50) g: (0-5) mol.

[0010] Further, the ratio of the Schiff base silane coupling agent, thermosetting resin, alkoxysilane, organic acid, water and transition metal salt is (10-20) g: (140-160) g: (100-200) g: (0-10) g: (0-44.85) g: (0-0.022) mol, preferably 14.41 g: 150 g: 140 g: (0-9.74) g: 44.85 g: (0-0.022) mol;

[0011] The thermosetting resin is a phenolic resin or a modified phenolic resin, preferably a boron phenolic resin or a modified boron phenolic resin; the alkoxysilane is methyltriethoxysilane, isobutyltriethoxysilane, γ-aminopropyltriethoxysilane, trialkoxysilane or dialkoxysilane; the organic acid is acetic acid, formic acid, propionic acid, butyric acid, citric acid, lactic acid, malic acid or tartaric acid; the transition metal salt is a nickel salt, an iron salt, a copper salt, a chromium salt, a cobalt salt, a scandium salt, a titanium salt, a vanadium salt, a manganese salt, a zinc salt, a rhodium salt or a palladium salt.

[0012] Furthermore, the transition metal salt is a transition metal chloride salt.

[0013] Furthermore, the ratio of the Schiff base silane coupling agent, the thermosetting resin, the alkoxysilane, the organic acid, the water and the transition metal salt is 14.41 g: 150 g: 140 g: (3.90-9.74) g: 44.85 g: 0 mol.

[0014] Furthermore, the ratio of the Schiff base silane coupling agent, the thermosetting resin, the alkoxysilane, the organic acid, the water and the transition metal salt is 14.41 g: 150 g: 140 g: 3.90 g: 44.85 g: 0.022 mol.

[0015] Furthermore, the Schiff base silane coupling agent is a product obtained by the reaction of aminoalkoxysilane and salicylaldehyde or its derivatives;

[0016] The mass ratio of the aminoalkoxysilane to salicylaldehyde or its derivative is 10:(3-5), preferably 10:4.41;

[0017] The aminoalkoxysilane is any one of 3-aminopropyltriethoxysilane, aminopropyltrimethoxysilane, bis(tert-butylamino)silane and 4-anilinotriethoxysilane, or a mixture of two or more thereof.

[0018] Furthermore, the Schiff base silane coupling agent is prepared by the following method: aminoalkoxysilane and salicylaldehyde or its derivatives are reacted in an organic solvent to obtain a Schiff base silane coupling agent; wherein the reaction temperature is 40-70°C, and the reaction time is 1-4 hours; the mass ratio of the aminoalkoxysilane to the organic solvent is 10:(50-200);

[0019] Preferably, the organic solvent is ethanol, the reaction temperature is 60° C., and the reaction time is 2 hours; the mass ratio of the aminoalkoxysilane to the organic solvent is 10:100.

[0020] The present invention also provides a method for preparing the above-mentioned Schiff base silane complex transition metal modified resin, the method comprising the following steps:

[0021] (a) adding a thermosetting resin, an alkoxysilane, a Schiff base silane coupling agent, water and an organic acid into an organic solvent for reaction, and obtaining a resin solution after the reaction is completed;

[0022] (b) adding an organic solvent solution of a transition metal salt to react, and removing the organic solvent after the reaction is completed to obtain an intermediate;

[0023] (c) solidifying the intermediate to obtain the product.

[0024] Furthermore, the organic solvent in step (a) and step (b) is an alcohol solvent; the reaction temperature in step (a) is 80-100° C., the reaction time is 2-8 hours, and the mass ratio of the thermosetting resin to the organic solvent is 150:(100-200); the reaction temperature in step (b) is 40-80° C., the reaction time is 2-8 hours, and the molar mass ratio of the transition metal salt to the organic solvent in the organic solvent solution of the transition metal salt is (0.002-0.022) mol:200g;

[0025] Preferably, the organic solvent in step (a) and step (b) is ethanol; the reaction temperature in step (a) is 80° C. and the reaction time is 4 hours; the reaction temperature in step (b) is 60° C. and the reaction time is 4 hours.

[0026] The present invention also provides the use of the Schiff base silane complex transition metal modified resin in heat protection materials, ablation resistant materials and fireproof materials.

[0027] Furthermore, the thermal protection material includes aircraft thermal protection structural material and engine thermal protection material.

[0028] The present invention synthesizes a silane coupling agent with a hydroxyl-substituted aromatic Schiff base structure, and uses traditional silane and thermosetting resin as raw materials. By adding a certain amount of coupling agent, on the one hand, the compatibility of silicone and thermosetting resin is significantly improved. On the other hand, the introduction of the Schiff base structure improves the system's ability to stably chelate transition metals, and the transition metals can be evenly introduced into the cross-linked network of the thermosetting resin. The combined effect of the two significantly improves the ablation resistance of the material. The material of the present invention has excellent ablation resistance and has broad application prospects in the field of thermal protection materials. It is suitable for preparing structural components and protective materials for structural components used in aircraft and related equipment and devices that need to withstand the harsh environment of high-temperature combustion gas and aerodynamic heat flow scouring.

[0029] The ablation resistance and heat resistance of the Schiff base silane coupling agent modified boron phenolic resin prepared by the present invention are significantly improved, among which the Schiff base silane coupling agent modified boron phenolic resin of Example 4 has the lowest linear ablation rate and the best ablation resistance; the Schiff base silane coupling agent modified boron phenolic resin of Example 5 has the highest 800°C thermal residual weight and the best heat resistance.

[0030] In the transition metal / Schiff base silane coupling agent modified boron phenolic resin prepared based on the Schiff base silane coupling agent modified boron phenolic resin of Example 4, under the condition of the same transition metal addition amount, when the transition metal is copper, the obtained copper / Schiff base silane coupling agent modified boron phenolic resin has the lowest linear ablation rate and the best ablation resistance; when the same transition metal is used, it is not the case that adding more transition metal to the Schiff base silane coupling agent modified boron phenolic resin is more beneficial to improving the heat resistance of the modified boron phenolic resin, but it is necessary to control the specific transition metal addition amount of the present invention.

[0031] The Schiff base silane coupling agent modified boron phenolic resin of the present invention has broad application prospects in the field of thermal protection materials, and is suitable for preparing structural components and protective materials for structural components used in aircraft and related equipment and devices that need to withstand the harsh environment of high-temperature combustion gas and aerodynamic heat flow scouring.

[0032] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0033] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The resin solution is prepared by a single-step method.

[0035] Figure 2 For SBPR and SNBPR resin solutions

[0036] Figure 3 Infrared spectra of Schiff base coupling agent modified boron phenolic resin (a) before curing, (b) during curing and (c) after curing; XPS (d) Si2p and (e) B1s spectra after curing of modified resin; (f) 29Si solid NMR spectrum of uncured resin; SEM morphology of brittle fracture surface and Si element mapping (g) SBPR 50-4 、(h)SBPR B50-4 .

[0037] Figure 4 (a) SAXS spectrum and (b) XRD spectrum of the cured resin.

[0038] Figure 5Transition metal / Schiff base silane coupling agent modified boron phenolic resin ethanol solution: (a) fluorescence spectrum, (c) UV spectrum; Iron / Schiff base silane coupling agent modified boron phenolic resin ethanol solution: (b) fluorescence spectrum, (d) UV spectrum; SFeBPR 50-3(11 / 9) Sample: (e) XPS, (f) TEM, (gj) mapping element distribution of Figure g.

[0039] Figure 6 (ah) Height cloud map and (ip) 3D morphology map of the sample surface after ablation for 30s: (a, i) pure boron phenolic resin, (b, j) SBPR B50-0 , (c, k)SBPR 50-0 , (d, l)SBPR 50-1 , (e, m)SBPR 50-2 , (f, n)SBPR 50-3 , (g, o)SBPR 50-4 , (h, p)SBPR B50-4 ; (q) profile line, (r) line ablation rate distribution and (s) width of the ablation retreat area.

[0040] Figure 7 Linear ablation rate (a) and mass ablation rate (b) of the sample after ablation for 30 seconds.

[0041] Figure 8 (a, c) Thermogravimetric curves of each hybrid resin in nitrogen and air atmosphere after curing and (b, d) thermal residual weight at 800°C.

[0042] Fig. 9 Thermal gravimetric loss curves of modified phenolic resin obtained with different transition metal addition amounts in nitrogen atmosphere. DETAILED DESCRIPTION

[0043] Boron phenolic resin (BPR): Shaanxi Taihang Fire Resistant Company, THC-400 boron phenolic resin, gel speed 70 ~ 100s / 200 ℃, free phenol content less than 7%, yellow block.

[0044] Methyltriethoxysilane (MTOS); 3-aminopropyltriethoxysilane (APTES); salicylaldehyde (SD); ethanol (Ethanol).

[0045] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.

[0046] Table 1 Raw material formula of each sample

[0047]

[0048]

[0049] Example 1: Boron phenolic resin (SBPR) modified by Schiff base silane coupling agent of the present invention 50-0 )

[0050] Step 1. Preparation of Schiff base silane coupling agent (ATSD)

[0051] Take 10g (0.045mol) 3-aminopropyltriethoxysilane, 4.41g (0.036mol) salicylaldehyde and 100g ethanol and add them into a flask. When the oil bath is heated to 60°C, keep it warm for 2h under inert atmosphere to obtain a bright yellow ethanol solution containing Schiff base silane coupling agent. The excess 3-aminopropyltriethoxysilane ensures that the salicylaldehyde in the system reacts completely, and the remaining 3-aminopropyltriethoxysilane in the system also plays a coupling role in the subsequent reaction.

[0052] Step 2. The Schiff base silane coupling agent of the present invention is modified with boron phenolic resin (SBPR 50-0 )

[0053] 150 g of boron phenolic resin and 200 g of ethanol were added to a flask, stirred at room temperature until the boron phenolic resin was completely dissolved, and then 140 g of methyltriethoxysilane was added, stirred until uniformly dispersed, and finally the ethanol solution of Schiff base silane coupling agent prepared in step 1 of Example 1 was added. The oil bath was heated to 80° C. and reacted for 4 h under an inert atmosphere to obtain a resin solution.

[0054] After the reaction was completed, the resin solution was concentrated by rotary evaporation and treated in a vacuum oven at 60° C. for 12 h to remove the solvent in the resin to obtain boron phenolic resin powder modified with Schiff base silane coupling agent.

[0055] The obtained modified boron phenolic resin powder is compression molded and cured, and the curing process is as follows: 110°C without pressure, maintained for 30 minutes; heating from 110°C to 140°C, with a heating rate of 5°C / min; keeping at 140°C for 30 minutes, and gradually pressurizing to 12-15MPa; heating from 140°C to 180°C, with a heating rate of 5°C / min, maintaining a pressure of 12-15MPa; keeping at 180°C for 2 hours, maintaining a pressure of 12-15MPa; heating from 180°C to 200°C, with a heating rate of 5°C / min, maintaining a pressure of 12-15MPa; keeping at 200°C for 1 hour, maintaining a pressure of 12-15MPa; finally, maintaining a pressure of 12-15MPa, and naturally cooling to room temperature to obtain a Schiff base silane coupling agent-modified boron phenolic resin ablation-resistant material.

[0056] Example 2-3, the present invention Schiff base silane coupling agent modified boron phenolic resin (Example 2SBPR 50-1 , Example 3SBPR 50-2 )

[0057] Take 150g of boron phenolic resin and SBPR according to Table 1 50-1 , SBPR 50-2 The corresponding amount of ethanol in the sample formula was added to the flask, stirred at room temperature until the boron phenolic resin was completely dissolved, and then 140g of methyltriethoxysilane was added, stirred until uniformly dispersed, and finally the Schiff base silane coupling agent solution prepared in step 1 of Example 1 was added. The oil bath was heated to 80°C, and the deionized water mixed solution (the amount added is shown in Table 1) was added to the flask through a constant pressure dropping funnel under inert atmosphere. After the addition was completed, the reaction was continued at 80°C for 4h to obtain a resin solution.

[0058] After the reaction was completed, the resin solution was concentrated by rotary evaporation and treated in a vacuum oven at 60° C. for 12 h to remove the solvent in the resin to obtain boron phenolic resin powder modified with Schiff base silane coupling agent.

[0059] The molding process is carried out and then cured. The curing process is the same as that in Example 1, and the ablation-resistant material SBPR containing a Schiff base silane coupling agent modified boron phenolic resin is obtained. 50-1 , SBPR 50-2 .

[0060] Example 4-5, Schiff base silane coupling agent modified boron phenolic resin (Example 4SBPR 50-3 , Example 5 SBPR 50-4 )

[0061] Take 150g of boron phenolic resin and 100g of ethanol and add them to a flask, stir at room temperature until the boron phenolic resin is completely dissolved, continue to add 140g of methyltriethoxysilane, stir until uniformly dispersed, and finally add the ethanol solution of Schiff base silane coupling agent prepared in step 1 of Example 1. Heat the oil bath to 80°C, and add acetic acid (addition amount corresponding to Table 1) and a mixed solution of deionized water (44.85g of deionized water) to the flask through a constant pressure dropping funnel under inert atmosphere. After the addition is completed, continue to react at 80°C for 4h to obtain a resin solution.

[0062] After the reaction was completed, the resin solution was concentrated by rotary evaporation and treated in a vacuum oven at 60° C. for 12 h to remove the solvent in the resin to obtain boron phenolic resin powder modified with Schiff base silane coupling agent.

[0063] The molding process is carried out and then cured. The curing process is the same as that in Example 1, and the ablation-resistant material SBPR containing a Schiff base silane coupling agent modified boron phenolic resin is obtained. 50-3 , SBPR 50-4 .

[0064] According to the results of Experimental Example 4 below, it can be seen that the line ablation rate of the Schiff base silane coupling agent modified boron phenolic resin prepared according to the method of Example 4 of the present invention is the lowest and the ablation resistance is the best. Therefore, Examples 6-16 are based on the Schiff base silane coupling agent modified boron phenolic resin of Example 4, and further provide a method for preparing a transition metal / Schiff base silane coupling agent modified boron phenolic resin.

[0065] Example 6-16, the present invention transition metal / Schiff base silane coupling agent modified boron phenolic resin (SXBPR 50-3(Y) ) Preparation of ablation-resistant materials

[0066] Table 2SXBPR 50 -3(Y) Sample Raw Materials List (SXBPR 50 -3(Y), X represents the type of transition metal; Y represents the molar number of transition metal / 0.0018)

[0067]

[0068] 1. Preparation of SFeBPR 50-3(11 / 9)

[0069] 0.5947 g (0.0022 mol Fe 3+ ) Ferric chloride is dissolved in 20 g of ethanol to prepare a ferric chloride ethanol solution.

[0070] Referring to the method of Example 4, a resin solution was prepared using the raw materials in Table 2 except for the transition metal and ethanol (for preparing the resin). After the resin solution was cooled to 60° C., an ethanol solution of ferric chloride was added dropwise to the flask through a constant pressure dropping funnel under an inert atmosphere. After the addition was completed, the reaction was continued at 60° C. for 4 h.

[0071] After the reaction is completed, the solvent in the resin is removed by rotary evaporation and vacuum oven equipment to obtain iron / Schiff base silane coupling agent modified boron phenolic resin powder (SFeBPR).

[0072] The molding process is carried out and then cured. The curing process is the same as that in Example 1, and the iron / Schiff base silane coupling agent modified boron phenolic resin ablation resistant material SFeBPR is obtained. 50-3(11 / 9) .

[0073] 2. Preparation of the remaining samples in Table 2

[0074] Refer to SFeBPR 50-3(11 / 9) The remaining samples in Table 2 were prepared by the preparation method.

[0075] Example 17: Preparation of Schiff base silane coupling agent of the present invention

[0076] Take 10g (0.045mol) 3-aminopropyltriethoxysilane, 4.41g (0.036mol) salicylaldehyde and 100g ethanol and add them into a flask. When the oil bath is heated to 60°C, keep it warm for 2h under inert atmosphere to obtain a bright yellow ethanol solution containing Schiff base silane coupling agent. The excess 3-aminopropyltriethoxysilane ensures that the salicylaldehyde in the system reacts completely, and the remaining 3-aminopropyltriethoxysilane in the system also plays a coupling role in the subsequent reaction.

[0077] Example 18: Preparation of Schiff base silane coupling agent of the present invention

[0078] Take 10g (0.045mol) 3-aminopropyltriethoxysilane, 3.42 (0.028mol) salicylaldehyde and 50g ethanol and add them into a flask. When the oil bath is heated to 70°C, keep it warm for 2h under inert atmosphere to obtain a bright yellow ethanol solution containing Schiff base silane coupling agent. The excess 3-aminopropyltriethoxysilane ensures that the salicylaldehyde in the system reacts completely, and the remaining 3-aminopropyltriethoxysilane in the system also plays a coupling role in the subsequent reaction.

[0079] Example 19: Preparation of Schiff base silane coupling agent of the present invention

[0080] Take 10g (0.045mol) 3-aminopropyltriethoxysilane, 4g (0.036mol) salicylaldehyde and 100g ethanol and add them into a flask. When the oil bath is heated to 65°C, keep it warm for 2h under inert atmosphere to obtain a bright yellow ethanol solution containing Schiff base silane coupling agent. The excess 3-aminopropyltriethoxysilane ensures that the salicylaldehyde in the system reacts completely, and the remaining 3-aminopropyltriethoxysilane in the system also plays a coupling role in the subsequent reaction.

[0081] The following is the preparation method of the control sample.

[0082] Comparative Example 1: Silane-modified boron phenolic resin (SBPR B50-0 )

[0083] Take 150g of boron phenolic resin, 150g of methyltriethoxysilane and 300g of ethanol and add them to a flask, stir at room temperature until completely dissolved. Heat the oil bath to 80°C and react for 4 hours under inert atmosphere. After the reaction is completed, remove the solvent in the resin by rotary evaporation and vacuum oven to obtain silane-modified boron phenolic resin powder.

[0084] The molding process is the same as that in Example 1, and the silane-modified boron phenolic resin ablation-resistant material (SBPR) is obtained. B50-0 ).

[0085] Comparative Example 2: Silane-modified boron phenolic resin (SBPR B50-4 )

[0086] Take 150g of boron phenolic resin, 150g of methyltriethoxysilane and 200g of ethanol and add them to a flask, stir at room temperature until completely dissolved. Heat the oil bath to 80°C, and add a mixed solution of acetic acid and deionized water (9.74g of acetic acid, 44.85g of deionized water) to the flask through a constant pressure dropping funnel under inert atmosphere. After the addition is complete, continue to react at 80°C for 4h. After the reaction is completed, remove the solvent in the resin by rotary evaporation and vacuum oven to obtain silane-modified boron phenolic resin powder.

[0087] The molding process is the same as that in Example 1, and the silane-modified boron phenolic resin ablation-resistant material (SBPR) is obtained. B50-4 ).

[0088] Comparative Example 3: Preparation of Cured Boron Phenolic Resin (BPR')

[0089] Boron phenolic resin powder BPR is used for compression molding and curing. The curing process is the same as that in Example 1, so as to obtain a boron phenolic resin ablation-resistant material (BPR').

[0090] The beneficial effects of the present invention are demonstrated by experimental examples below.

[0091] Experimental Example 1. Screening test of preparation method of transition metal / Schiff base silane coupling agent modified boron phenolic resin I. Experimental method

[0092] Taking Example 9 as an example, the preparation method thereof is to react a Schiff base silane coupling agent with a boron phenolic resin and methyl triethoxysilane at 80°C for a period of time, and then dropwise add Ni at 60°C. 2+ Perform low temperature chelation.

[0093] The screening control test used Schiff base silane coupling agent, boron phenolic resin, methyl triethoxysilane and Ni 2+ The single-step method is used for the reaction, and the specific steps are as follows:

[0094] 150g of boron phenolic resin and 200g of ethanol were added to a flask, stirred at room temperature until the boron phenolic resin was completely dissolved, and then 140g of methyltriethoxysilane was added, stirred until uniformly dispersed, and finally the ethanol solution of Schiff base silane coupling agent prepared in step 1 of Example 1 was added. The oil bath was heated to 80°C, and the nickel chloride ethanol solution was added dropwise to the flask through a constant pressure dropping funnel under inert atmosphere. After the addition was completed, the reaction was continued for 4h.

[0095] 2. Experimental Results

[0096] The following problems may occur in the resin solution prepared by the screening control test method:

[0097] After about 1h of reaction, Figure 1 It can be seen that the resin solution is opaque and a large amount of precipitate is precipitated in the reaction system, indicating that the silane condenses rapidly, leading to severe phase separation.

[0098] In Example 9 of the present invention, two different temperatures are used for pre-reaction and chelation reaction. First, the Schiff base silane coupling agent and the boron phenolic resin are pre-reacted at 80°C for 4 hours, and then the system is cooled to 60°C to obtain the SBPR resin solution. An ethanol solution containing nickel chloride is added dropwise to perform a low-temperature chelation reaction. The condensation degree of silane in the system is controlled to obtain the SNBPR resin solution. The SBPR and SNBPR resin solutions are uniform and transparent. 2+ After chelation, the color of the resin deepens (e.g. Figure 2 ), long-term non-fading, indicating Ni 2+ Stable coordination in the system.

[0099] The experimental results show that the resin solution obtained by the two-stage method in Example 9 of the present invention is stable and transparent. Metal ion chelation is carried out by the method of Example 9 of the present invention, and the metal ions are stably coordinated in the system. After chelation, the color of the resin deepens and does not fade after being left for a long time.

[0100] Experimental Example 2: Structural Characterization of Boron Phenolic Resin Modified by Schiff Base Silane Coupling Agent of the Present Invention

[0101] 1. Experimental Methods

[0102] Tested by infrared spectroscopy Figure 3 (ac) and 29Si solid state NMR Figure 3 (f) Characterize the structural changes of the modified resin before, during and after curing. Figure 3 (d, e) Characterization of the structural differences of the modified resin after curing. The organic silicon phase and Si element distribution were characterized by the brittle fracture scanning electron microscopy (SEM) morphology of the cured resin and its surface scanning (Mapping) mode. Figure 3 (g, h).

[0103] About SBPR 50-0 and SBPR 50-3 Small angle X-ray diffraction (SAXS) test was performed, and the experimental results are as follows Figure 4 As shown in a, each cured resin was tested by X-ray diffractometer (XRD), and the experimental results are shown in Figure 4 As shown in b.

[0104] 2. Experimental Results

[0105] Figure 3 a and Figure 3 In the infrared spectrum of the resin before and after curing, 1635 cm -1The -CH=N peak at 960cm -1 and 910cm -1 The peaks of Si-O-Ph and Si-OB indicate that the organosilicon reacts with phenolic hydroxyl and boric hydroxyl groups to introduce siloxane into the phenolic resin in the form of covalent bonds.

[0106] Figure 3 b medium 960cm -1 The Si-O-Ph bond strength at 1226 cm-1 is gradually weakened, indicating that it will be lost to a certain extent during the curing process. -1 The Ar-OH peak gradually weakens, indicating that as the curing reaction proceeds, the B-OH and Ph-OH in the system gradually react completely.

[0107] Figure 3 As can be seen in Figure d, with the increase in the amount of deionized water / acetic acid added and the decrease in the amount of ethanol used, the relative content of Si-O-Si bonds in the Si element in the system gradually increased, from 32.3% in SBPR50-0 to 53.4% ​​in SBPR50-4, indicating that the degree of silane self-condensation in the system continued to increase.

[0108] Figure 3 e indicates that the B element in the cured resin participates in the resin curing by forming BOC, BOB and BO-Si, and the appearance of BO-Si bonds once again proves that silicone reacts with boron hydroxyl groups to connect siloxane to phenolic resin in the form of covalent bonds.

[0109] Figure 3 f shows that with the increase of deionized water / acetic acid addition and the decrease of ethanol usage, the number of ethoxy groups in the system continues to decrease, indicating that the degree of silane self-condensation increases.

[0110] contrast Figure 3 g and Figure 3 hIt can be seen that when the amount of deionized water / acetic acid added is the same as that of ethanol, the addition of Schiff base coupling agent causes the silicone to be phased by micron size in the phenolic resin ( Figure 3 h) The system was transformed into a homogeneous system and no obvious phase separation was observed.

[0111] The experimental results show that the present invention can change the degree of silane self-condensation in the system by adjusting the amount of deionized water, acetic acid and ethanol in the formula. The present invention continuously improves the degree of silane self-condensation in the system by increasing the amount of deionized water, acetic acid and ethanol in the formula. At the same time, the present invention adds a Schiff base coupling agent, and when the degree of silane self-condensation in the system is not much different, the organosilicon in the system is transformed from a micron-scale phase to a homogeneous system, which significantly improves the compatibility of organosilicon and boron phenolic resin.

[0112] Figure 4 aAs you can see, SBPR 50-0 The SAXS curve of the sample has no scattering peak, indicating that there is no microstructure; SBPR 50-3 The SAXS curve of the sample shows a weak scattering shoulder. Calculated by the Bragg formula (L=2π / q), the average distance between adjacent organic silicon phases is 14.3 nm. Figure 4 b It can be seen that there is a passive amorphous diffraction peak at about 10.7°, corresponding to the organosilicon phase; for SBPR without adding Schiff base coupling agent B50-4 The peak intensity of the sample increased significantly and the peak shape became narrower, indicating that the size of the organosilicon phase was larger. The experimental results once again proved that the addition of the Schiff base coupling of the present invention can significantly improve the compatibility of organosilicon with boron phenolic resin.

[0113] Experimental Example 3: Structural Characterization of Boron Phenolic Resin Modified by Transition Metal / Schiff Base Silane Coupling Agent of the Present Invention I. Experimental Method

[0114] The fluorescence spectra of the boron phenolic resin modified by the transition metal / Schiff base silane coupling agent in Example 6-16 were detected by fluorescence spectrometer (using ethanol as solvent). The experimental results are as follows: Figure 5 a and Figure 5 b; UV-visible-near infrared spectrophotometer was used to detect the UV spectrum of the boron phenolic resin modified by the transition metal / Schiff base silane coupling agent of Example 6-16 (with ethanol as solvent), and the experimental results are as follows Figure 5 c and Figure 5 d; X-ray electron spectroscopy (XPS) and TEM characterization were performed on the iron / Schiff base silane coupling agent modified boron phenolic resin in Example 16. The results are as follows Figure 5 Ej.

[0115] 2. Experimental Results

[0116] Depend on Figure 5 a It can be seen that after adding equal amounts of different metal ions, the system all underwent fluorescence quenching, proving the interaction between transition metals and Schiff base structures; according to the degree of quenching, it was found that the system had a strong affinity for Fe 3+ Cr 3+ and Cu 2+ The recognition ability is better than other transition metal ions. Figure 5 c It can be seen that after adding equal amounts of different metal ions, the UV absorption spectra have obvious changes (red shift or blue shift of Schiff base n–π* peak; change of peak intensity, etc.), indicating that the Schiff base structure has coordinated with different metal ions to a certain extent; Figure 5 b It can be seen that the fluorescence quenching phenomenon increases with the Fe 3+ The concentration increases gradually; Figure 5 d It can be seen that the addition of Fe 3+After that, the typical ligand-to-metal charge transfer transition (LMCT) of metal complexes appeared at 550nm, and the intensity increased with the increase of Fe 3+ The fluorescence quenching continued to increase with the increase of the added amount, indicating that the previous fluorescence quenching was not caused by the destruction of the Schiff base structure.

[0117] Depend on Figure 5 e It can be seen that the C=N peak in some ATSD is closely related to Fe 3+ Coordination occurs, sharing electrons, which reduces the electron cloud density around the N atom, so the peak moves toward the direction of high binding energy, indicating that Fe 3+ Successfully coordinated with -CH=N in the ATSD structure; Figure 5 It can be seen that a Si-ON-Fe-rich phase was observed in the hybrid resin, which once again proved that ATSD successfully chelated transition metals.

[0118] Experimental Example 4: Ablation Performance Test of the Modified Boron Phenolic Resin of the Present Invention

[0119] 1. Experimental Methods

[0120] According to the ablation resistance test standard GJB 323A-1996; heat flux density: 4000kW / m 2 ; Ablation time: 30s, ablation resistance test. The experimental results are as follows Figure 6 (qs), Figure 7 And as shown in Table 2.

[0121] Table 2 Results of line ablation rate and mass ablation rate of each cured resin

[0122]

[0123]

[0124] It can be seen that compared with the cured boron phenolic resin (BPR') of control example 3 and the silane-modified boron phenolic resin of control examples 1 and 2, the linear ablation rate of the Schiff base silane coupling agent modified boron phenolic resin of Examples 3-5 of the present invention is significantly reduced, among which the linear ablation rate of the Schiff base silane coupling agent modified boron phenolic resin of Example 4 is the lowest and the ablation resistance is the best.

[0125] Further comparison of the transition metal / Schiff base silane coupling agent modified boron phenolic resins of Examples 9-11 of the present invention revealed that, under the same transition metal addition amount, when the transition metal was copper, the obtained copper / Schiff base silane coupling agent modified boron phenolic resin had the lowest linear ablation rate and the best ablation resistance.

[0126] Experimental Example 5 Heat resistance test of the modified boron phenolic resin of the present invention

[0127] The thermal gravimetric curves of the cured samples in nitrogen (N2) and air (Air) atmospheres were tested by a thermogravimetric analyzer (TG) to obtain the thermal residual weight at 800°C. Figure 8-9 As shown in Table 3

[0128] Table 3 800℃ heat residual weight of each cured resin (%)

[0129]

[0130] from Figure 8 It can be seen from Table 3 that, whether in nitrogen or air atmosphere, the 800°C thermal residual weight of the boron phenolic resin modified by the Schiff base silane coupling agent of the present invention gradually increases with the increase of the degree of silane self-condensation, among which the boron phenolic resin modified by the Schiff base silane coupling agent in Example 5 has the highest 800°C thermal residual weight in nitrogen atmosphere and in air atmosphere, and has the best heat resistance.

[0131] Further from Fig. 9 As can be seen from Table 3, compared with the boron phenolic resin modified by the Schiff base silane coupling agent of Example 4, the boron phenolic resin SFeBPR modified by the iron / Schiff base silane coupling agent of Example 11 of the present invention is 50-3(1 / 9) The 800℃ thermal residual weight increased, but the iron / Schiff base silane coupling agent modified boron phenolic resin SFeBPR of Example 16 50-3(11 / 9) The 800℃ thermal residual weight is reduced. This shows that when the transition metal is the same, adding more transition metals to the boron phenolic resin modified by Schiff base silane coupling agent is not conducive to improving the heat resistance of the modified boron phenolic resin, but it is necessary to control the specific amount of transition metal added.

[0132] In summary, the present invention synthesizes a silane coupling agent with a hydroxyl-substituted aromatic Schiff base structure, and uses traditional silane and thermosetting resin as raw materials. By adding a certain amount of coupling agent, on the one hand, the compatibility of silicone and thermosetting resin is significantly improved. On the other hand, the introduction of the Schiff base structure improves the system's ability to stably chelate transition metals, and the transition metals can be evenly introduced into the cross-linked network of the thermosetting resin. The combined effect of the two significantly improves the ablation resistance of the material. The material of the present invention has excellent ablation resistance and has broad application prospects in the field of thermal protection materials. It is suitable for preparing structural components and protective materials for structural components used in aircraft and related equipment that need to withstand the harsh environment of high-temperature combustion gas and aerodynamic heat flow scouring.

Claims

1. A Schiff base silane complex transition metal modified resin, characterized in that: It is a composite material prepared from Schiff base silane coupling agent, thermosetting resin, alkoxysilane, organic acid, water and transition metal salt as raw materials; The ratio of the Schiff base silane coupling agent, the thermosetting resin, the alkoxysilane, the organic acid, the water and the transition metal salt is (0.01-50) g: (100-500) g: (100-500) g: (0-50) g: (0-50) g: (0-5) mol.

2. The Schiff base silane complex transition metal modified resin according to claim 1, characterized in that: The ratio of the Schiff base silane coupling agent, thermosetting resin, alkoxysilane, organic acid, water and transition metal salt is (10-20) g: (140-160) g: (100-200) g: (0-10) g: (0-44.85) g: (0-0.022) mol, preferably 14.41 g: 150 g: 140 g: (0-9.74) g: 44.85 g: (0-0.022) mol; The thermosetting resin is a phenolic resin or a modified phenolic resin, preferably a boron phenolic resin or a modified boron phenolic resin; the alkoxysilane is methyltriethoxysilane, isobutyltriethoxysilane, γ-aminopropyltriethoxysilane, trialkoxysilane or dialkoxysilane; the organic acid is acetic acid, formic acid, propionic acid, butyric acid, citric acid, lactic acid, malic acid or tartaric acid; the transition metal salt is a nickel salt, an iron salt, a copper salt, a chromium salt, a cobalt salt, a scandium salt, a titanium salt, a vanadium salt, a manganese salt, a zinc salt, a rhodium salt or a palladium salt.

3. The Schiff base silane complex transition metal modified resin according to claim 2, characterized in that: The ratio of the Schiff base silane coupling agent, the thermosetting resin, the alkoxysilane, the organic acid, the water and the transition metal salt is 14.41 g: 150 g: 140 g: (3.90-9.74) g: 44.85 g: 0 mol.

4. The Schiff base silane complex transition metal modified resin according to claim 3, characterized in that: The ratio of the Schiff base silane coupling agent, the thermosetting resin, the alkoxysilane, the organic acid, the water and the transition metal salt is 14.41 g: 150 g: 140 g: 3.90 g: 44.85 g: 0.022 mol.

5. The Schiff base silane complex transition metal modified resin according to any one of claims 1 to 4, characterized in that: The Schiff base silane coupling agent is a product obtained by the reaction of aminoalkoxysilane and salicylaldehyde or its derivatives; The mass ratio of the aminoalkoxysilane to salicylaldehyde or its derivative is 10:(3-5), preferably 10:4.41; The aminoalkoxysilane is any one of 3-aminopropyltriethoxysilane, aminopropyltrimethoxysilane, bis(tert-butylamino)silane and 4-anilinotriethoxysilane, or a mixture of two or more thereof.

6. The Schiff base silane complex transition metal modified resin according to any one of claims 1 to 5, characterized in that: The Schiff base silane coupling agent is prepared by the following method: aminoalkoxysilane and salicylaldehyde or its derivatives are reacted in an organic solvent to obtain a Schiff base silane coupling agent; wherein the reaction temperature is 40-70° C., and the reaction time is 1-4 hours; and the mass ratio of the aminoalkoxysilane to the organic solvent is 10:(50-200); Preferably, the organic solvent is ethanol, the reaction temperature is 60° C., and the reaction time is 2 hours; the mass ratio of the aminoalkoxysilane to the organic solvent is 10:

100.

7. A method for preparing the Schiff base silane complex transition metal modified resin according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (a) adding a thermosetting resin, an alkoxysilane, a Schiff base silane coupling agent, water and an organic acid into an organic solvent for reaction, and obtaining a resin solution after the reaction is completed; (b) adding an organic solvent solution of a transition metal salt to react, and removing the organic solvent after the reaction is completed to obtain an intermediate; (c) solidifying the intermediate to obtain the product.

8. The method according to claim 7, characterized in that: The organic solvent in step (a) and step (b) is an alcohol solvent; the reaction temperature in step (a) is 80-100° C., the reaction time is 2-8 hours, and the mass ratio of the thermosetting resin to the organic solvent is 150:(100-200); the reaction temperature in step (b) is 40-80° C., the reaction time is 2-8 hours, and the molar mass ratio of the transition metal salt to the organic solvent in the organic solvent solution of the transition metal salt is (0.002-0.022) mol:200g; Preferably, the organic solvent in step (a) and step (b) is ethanol; the reaction temperature in step (a) is 80° C. and the reaction time is 4 hours; the reaction temperature in step (b) is 60° C. and the reaction time is 4 hours.

9. Use of the Schiff base silane complex transition metal modified resin according to any one of claims 1 to 6 in thermal protection materials, ablation resistant materials and fireproof materials.

10. The use according to claim 9, characterized in that: The thermal protection materials include aircraft thermal protection structural materials and engine thermal protection materials.

Citation Information

Patent Citations

  • Triazine-silicon-containing Schiff base flame retardant and synthetic method thereof

    CN108948348A

  • Composition for sealing material

    JP1995316538A

  • Method of manufacturing silane crosslinking resin molding, and molding using the same

    JP2012149162A

  • Process for preparing a silicone resin-modified phenolic resin

    US5177157A